MECHANISMS OF FORMING OF STRUCTURE, PHASE COMPOSITION AND CHARACTERISTICS OF MECHANICALLY ALLOYED COPPER COMPOSITIONS - F. G. Lovshenko; G. F. Lovshenko (Литьë и металлургия)
Mechanisms of formation of structure of phase composition and characteristics of dispersion strengthened granulated compositions on the basis of copper produced by method of reactionary mechanical alloying are determined.